Floating lidar as an advanced offshore wind speed measurement technique: current technology status and gap analysis in regard to full maturity. Issue 5 (9th May 2017) - Gottschall, Julia; Gribben, Brian; Stein, Detlef; Würth, Ines
Abstract : Floating lidar was introduced in 2009 as an offshore wind measurement technology focusing on the specific needs of the wind industry with regard to wind resource assessment applications. Floating lidar systems (FLS) are meant to replace an offshore met mast, being significantly cheaper and saving an essential part of project upfront investment costs. But at the same time, they need to overcome particular challenges—these are (1) the movement of the sea imparting motion on the buoy and the lidar, and the subsequent challenge of maintaining wind speed and direction accuracy, and (2) the remoteness of the deployed system in an extremely challenging environment necessitating robust, autonomous and reliable operation of measurement, power supply, data logging, and communication systems. The issue of motion influences was investigated in a number of studies and is to be checked and monitored in offshore trials of individual FLS realizations. In trials to date, such influences have been demonstrated to be negligibly or manageably small with the application of motion reduction or compensation strategies. Thereby, it is possible to achieve accurate wind measurement data from FLS. The second kind of challenge is tackled by implementing a sufficiently robust and reliable FLS design. Recommended practices collected by a working group within the International Energy Agency (IEA) Wind Task 32 and within the UK offshore wind accelerator program offer guidance for FLS design and configuration, and furthermore set requirements for trialing the system types and individual devices in representative offshore conditions. WIREs Energy Environ 2017, 6:e250. doi: 10.1002/wene.250 This article is categorized under: Wind Power > Science and Materials Wind Power > Climate and Environment Abstract : Degrees of freedom of an exemplary floating lidar system in the fixed coordinate system of the sea environment. (Reprinted with permission from Ref 7. Copyright 2016 Carbon Trust)